What are the association patterns between handgrip strength and adverse health conditions? A topical review. (February 2020) - McGrath, Ryan; Johnson, Nathaniel; Klawitter, Lukus; Mahoney, Sean; Trautman, Kara; Carlson, Caroline; Rockstad, Ella; Hackney, Kyle J
Measures of handgrip strength can be used to conveniently assess overall muscle strength capacity. Although stand-alone measures of handgrip strength provide robust health information, the clinical meaningfulness to determine prevention and treatment options for weakness remains limited because the etiology of muscle weakness remains unclear. Moreover, clinical outcomes associated with handgrip strength are wide-ranging. Therefore, disentangling how handgrip strength is associated with health conditions that are metabolically or neurologically driven may improve our understanding of the factors linked to handgrip strength. The purpose of this topical review was to highlight and summarize evidence examining the associations of handgrip strength with certain health outcomes that are metabolically and neurologically driven. From this perusal of the literature, we posit that stand-alone handgrip strength be considered an umbrella assessment of the body systems that contribute to strength capacity, and a panoptic measurement of muscle strength that is representative of overall health status, not a specific health condition. Recommendations for future strength capacity–related research are also provided.